Diagnostic accuracy of the faecal immunochemical test for colorectal cancer in symptomatic patients: comparison with NICE and SIGN referral criteria. (August 2014) - Cubiella, J.; Salve, M.; Díaz‐Ondina, M.; Vega, P.; Alves, M. T.; Iglesias, F.; Sánchez, E.; Macía, P.; Blanco, I.; Bujanda, L.; Fernández‐Seara, J.
Abstract Aim The diagnostic accuracy of the faecal immunochemical test (FIT) at a 100 ng/ml threshold for colorectal cancer (CRC) was compared with National Institute for Health and Care Excellence (NICE) and the Scottish Intercollegiate Guidelines Network (SIGN) referral criteria. Method A multicentre, prospective, blind study of diagnostic tests was carried out in two Spanish health areas. In 787 symptomatic patients referred for a diagnostic colonoscopy, we determined whether patients met NICE and SIGN referral criteria. All patients performed one FIT determination (OCsensor™). The sensitivity and specificity for CRC detection were determined with McNemar's test. The diagnostic odds ratio as well as the number needed to scope (NNS) to detect a CRC were calculated. Results We detected CRC in 97 (12.3%) patients; 241 (30.6%) had an FIT ≥ 100 ng/ml and 300 (38.1%) and 473 (60.1%) met NICE and SIGN referral criteria. The FIT had a higher sensitivity for CRC detection than NICE criteria (87.6%, 61.9%; P < 0.001) and SIGN criteria (82.5%; P = 0.4). The specificity of FIT was also higher than NICE and SIGN criteria (77.4%, 65.2%, 42.7%; P < 0.001). The odds ratios of FIT, NICE and SIGN criteria for the diagnosis of CRC were 24.24 (95% CI 12.91–45.53), 3.04 (95% CI 1.96–4.71) and 3.51 (95% CI 2.03–6.06). The NNS to detect a CRC in individuals with an FIT ≥ 100 ng/ml was 2.83 (95% CI 2.4–3.41) and in individuals who met NICE and SIGN criteria it was 5 (95% CI 3.98–6.37) and 5.95 (95% CI 4.85–7.35). Conclusion Our study suggests that FIT is more accurate for the detection of CRC than the current NICE and SIGN referral criteria in symptomatic patients referred for colonoscopy.